2022
DOI: 10.3389/fgene.2022.977322
|View full text |Cite
|
Sign up to set email alerts
|

The cuproptosis-related signature predicts prognosis and indicates immune microenvironment in breast cancer

Abstract: Breast cancer (BC) is the most diagnosed cancer in women. Cuproptosis is new regulated cell death, distinct from known death mechanisms and dependent on copper and mitochondrial respiration. However, the comprehensive relationship between cuproptosis and BC is still blank until now. In the present study, we acquired 13 cuproptosis-related regulators (CRRs) from the previous research and downloaded the RNA sequencing data of TCGA-BRCA from the UCSC XENA database. The 13 CRRs were all differently expressed betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 67 publications
0
30
0
Order By: Relevance
“…The area under the ROC curve in both the training and validation sets at 1, 3 and 5 years was (AUC) 0.686, 0.722 and 0.727, and 0.626, 0.663 and 0.678, respectively ( Figure 4 F and Figure 5 C). In addition, we compared our risk model with other established models and found that the AUC of our risk model was higher than that of others ( Figure S3A–F ) [ 17 , 18 ].…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…The area under the ROC curve in both the training and validation sets at 1, 3 and 5 years was (AUC) 0.686, 0.722 and 0.727, and 0.626, 0.663 and 0.678, respectively ( Figure 4 F and Figure 5 C). In addition, we compared our risk model with other established models and found that the AUC of our risk model was higher than that of others ( Figure S3A–F ) [ 17 , 18 ].…”
Section: Resultsmentioning
confidence: 88%
“…Our study also showed some limitations. Firstly, Jia li et al [ 18 ] recently reported a model based on 13 differentially expressed cuproptosis regulators (between breast cancer and normal samples) selected from the original report firstly discovering cuproptosis [ 5 ], which could efficiently predict prognosis and even response to immunotherapy. Our study applied expanded cuproptosis-related DEGs according to different studies [ 5 , 13 , 14 , 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al [ 32 ] found the involvement of cuproptosis-related genes regulation in Hepatocellular carcinoma (HCC). Li et al [ 33 ] develop the cuproptosis-related prognostic signature to predict the prognosis of breast cancer (BC) through the Cox and Lasso regression analyses. However, studies of the function of CRLs in colorectal cancer (CRC) remain limited.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies mainly focused on the relationship between cuproptosis-related genes and breast cancer ( 67 , 68 ). Our study included not only cuproptosis-related genes but also copper metabolism-related genes to perform a comprehensive analysis of the role of copper-related genes in breast cancer development.…”
Section: Discussionmentioning
confidence: 99%